Efficacy of a nicotine mouth spray in smoking cessation: a randomised, double-blind trial - Tønnesen, Philip; Mann, Karl (The European respiratory journal, 2012)
A nicotine mouth spray has advantages over other acute forms of nicotine replacement therapy, such as a faster uptake of nicotine and faster relief of craving. This multicentre, randomised (2:1), double-blind, placebo-controlled efficacy and safety study evaluated self-reported, carbon monoxide-verified continuous abstinence from smoking from week 2 until weeks 6, 24, and 52 in 479 smokers (≥1 cigarette per day) who were treated with either active (n=318) or placebo (n=161) spray for 12 weeks and low-intensity counselling at three smoking cessation clinics in Denmark and Germany. Active treatment yielded significantly higher continuous abstinence rates than placebo from week 2 until week 6 (26.1% versus 16.1%; relative success rate (RR) 1.62, 95% CI 1.09-2.41), week 24 (15.7% versus 6.8%; RR 2.30, 95% CI 1.23-4.30), and week 52 (13.8% versus 5.6%; RR 2.48, 95% CI 1.24-4.94). Most adverse events were mild to moderate, and 9.1% of subjects on active spray withdrew due to adverse events, compared to 7.5% on placebo. The overall rate of treatment-related adverse events was 87.4% with active spray versus 71.4% with placebo spray. Nicotine mouth spray delivered significantly higher 6-, 24- and 52-week continuous abstinence rates than placebo.